2010
DOI: 10.1111/j.1744-7909.2010.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Chloroplast FtsH, var2 and Suppressors of var2 Leaf Variegation: a Review

Abstract: Variegation mutants are ideal model systems to study chloroplast biogenesis. We are interested in variegations whose green and white-sectored leaves arise as a consequence of the action of nuclear recessive genes. In this review, we focus on the Arabidopsis var2 variegation mutant, and discuss recent progress toward understanding the function of VAR2 and the mechanism of var2-mediated variegation. VAR2 is a subunit of the chloroplast FtsH complex, which is involved in turnover of the Photosystem II reaction ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 90 publications
(191 reference statements)
2
97
0
1
Order By: Relevance
“…The build up of the thylakoids requires the import of proteins within the plastid. A thylakoid Sec translocase subunit (SECA1, Solyc01g080840) is essential for chloroplast biogenesis (Liu et al, 2010b). Interestingly, the FtsH and EGY1 proteins decrease in abundance, mostly between the B and R stages, which correlates well with the dismantling of the thylakoid membranes, while SECA was present only at the MG stage, indicating an early end to the provision of material for thylakoid biogenesis.…”
Section: Loss Of the Machinery For The Build Up Of Thylakoids And Phomentioning
confidence: 92%
“…The build up of the thylakoids requires the import of proteins within the plastid. A thylakoid Sec translocase subunit (SECA1, Solyc01g080840) is essential for chloroplast biogenesis (Liu et al, 2010b). Interestingly, the FtsH and EGY1 proteins decrease in abundance, mostly between the B and R stages, which correlates well with the dismantling of the thylakoid membranes, while SECA was present only at the MG stage, indicating an early end to the provision of material for thylakoid biogenesis.…”
Section: Loss Of the Machinery For The Build Up Of Thylakoids And Phomentioning
confidence: 92%
“…These Clp proteases formed a chaperone complex to drive the import of proteins into the plastids, cleave the transit peptide, and recycle plastid components. In Arabidopsis, knocking out most members of the Clp protease family results in reduced plant growth with pale-green or variegated leaf phenotype, indicating the crucial role of the Clp complex in chloroplast development (Meinke et al, 2008;Liu et al, 2010;Olinares et al, 2011). Previous studies have revealed that the Clp complex, one of the prominent complexes, increases in abundance during the transition from proplastids or etioplasts into chloroplasts (Kanervo et al, 2008;Majeran et al, 2010).…”
Section: Stability In Protein Import Loss Of Ribosome Assembly Andmentioning
confidence: 99%
“…Instead, both Arabidopsis and rice show significant coexpression with tubulin-like Fts proteins found in the chloroplast thylakoid membrane that show homology to bacterial cell division genes (Jen et al, 2006;Jung et al, 2008a;Karamoko et al, 2011). Chloroplast division in plant cells requires the coordinated action of the tubulin-like FtsZ ring inside the chloroplast and the dynamin-like ring outside (Osteryoung et al, 1998;Osteryoung and McAndrew, 2001;Liu et al, 2010b;Pogson and Albrecht, 2011). The rice FtsZ gene (Os04g56970) is predicted to be involved in chloroplast division and was found to be significantly regulated by Cga1 expression in both microarray and quantitative reverse transcription (qRT)-PCR (Fig.…”
Section: Cga1 Modifies the Expression Of Important Chloroplast-localimentioning
confidence: 99%